Interpretasi Makna Kehendak Bebas Menurut St. Maximus - Eka Kurniawan Zebua; Hendi Wijaya (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
This article analyzes the thoughts of Father Philokalia St. Maximus on Free Will. The purpose of this study is to explain the true meaning of free will. Because free will is God's gift in man which functions as human power to be responsible for everything he thinks, both to himself and to others. Therefore, through free will, man can do whatever God wants in his life. In this article, we use literature studies by examining the thoughts of St. Maximus, journals, and other books. Finally, this research produces a theological meaning regarding human free will that is in accordance with God's will, namely free will not to sin, but free will that brings humans closer to God.